Sumber Informasi Orang Tua Siswa Sekolah Dasar tentang Pencegahan Kekerasan Seksual pada Anak - Rachma Noer Fadhilah; Tetti Solehati; Sukmawati Sukmawati (Universitas Ngudi Waluyo, 2025)
Abstract Child sexual abuse (CSA) in Indonesia remains a serious issue, with the number of cases continuing to rise. One of the causes of CSA is the lack of exposure to information among parents, compounded by the perception that the topic is taboo. Parents need to obtain adequate information to educate their children about preventing CSA. Information can be accessed from various sources, such as individuals, conventional media, and social media. This study aims to identify the sources of information about CSA prevention that parents utilize. The research was conducted in October 2024 using a descriptive quantitative research design with a sample of 100 parents of students in grades 1–6 at elementary schools in the Dayeuhkolot subdistrict, Bandung Regency. The sampling technique employed was stratified random sampling. The instrument used was a questionnaire developed by Solehati, (2022) titled